Sosialisasi Penerapan Manajemen Keuangan Guna Mengatasi Hambatan Pengembangan Ekonomi Masyarakat di RT.11 RW.04 Kelurahan Surabaya Kota Bengkulu - Abi, Yudi Irawan; Wijaya, Ermy; Januarsih, Ayu; Melinda, Tri Febrina; Putri, Lydia Gustina (Jurnal Dehasen Mengabdi, 2024)
Definition of Financial Management according to J.L. Massie Financial management is an operational activity that is responsible for obtaining and using the funds needed for effective and efficient operations. The application of financial management in the scope of community life is also very necessary for the development of the community's economy. However, there are still many people who have obstacles to their economic development due to a lack of understanding and knowledge about good and correct financial management. Therefore, our Unived Management lecturer and student service team provides knowledge and understanding of the Financial Management System which aims to overcome obstacles to community economic development. The method we use is socialization in the form of discussions, and delivering material to several local residents as representatives of the community where we carry out our service. The results of our service have very helpful benefits for the community who are the object of our socialization